Maternal and neonatal vitamin D deficiency, vitamin D-related gene polymorphism and birth outcomes - Lee, Siew Siew (2019)
Epidemiology data have shown widespread vitamin D deficiency in several populations. However, up to date, data on vitamin D status of women and neonates living in Malaysia is scarce to inform the development of national recommendation for vitamin D supplementation for pregnant women and newborns. In addition, the associations between low maternal and cord 25-hydroxyvitamin D (25OHD) with size at birth is inconsistent, and the plausible mechanisms of action of vitamin D on fetal growth have remained unexplored. Therefore, this study aims to determine the prevalence of vitamin D deficiency in pregnant women and newborns at delivery as well as factors associated with the deficiency. At the same time, this study also sought to investigate the associations between maternal and cord total vitamin D deficiency, and vitamin D polymorphism with birth outcomes concomitantly. Healthy pregnant women and neonates (217 dyads) were recruited from Hospital Serdang, Selangor, Malaysia. Venous blood was collected from pregnant mothers before delivery. Umbilical cord blood was collected from the severed umbilical cord after the delivery of the baby but before the delivery of the placenta. Maternal and cord total 25OHD levels were measured by using a validated ultra-high-performance liquid chromatography (UHPLC) method. Vitamin D Receptor (VDR) polymorphism (rs2228570) was determined using High-Resolution Melting (HRM), while Group- Specific component (GC) polymorphisms (rs4588 and rs7041) were determined using restriction fragment length polymorphism (RFLP). The result showed that the median maternal total 25OHD was 29.8 nmol/L (Interquartile Range [IQR] 18.8-43.5 nmol/L), with 50.2% of pregnant women had vitamin D deficiency (25OHD <30 nmol/L). Multivariate analysis showed that the risk factors of maternal vitamin D deficiency (25OHD <30nmol/L) were age, veiled clothing, homozygous mutant for GC rs7041. On the other hands, the protective factors for maternal vitamin D deficiency were vitamin D intake from food and supplements. The median cord total 25OHD was 22.0 nmol/L (IQR 15.5-31.0 nmol/L), which 71.4% of newborns had vitamin D deficiency (25OHD <30 nmol/L). Consistent with the previous studies, maternal status was the best predictor of neonatal vitamin D deficiency (25OHD < 30nmol/L). In the present study, neonates born from a mother with vitamin D deficiency had eight times higher risk of deficiency. Moreover, factors that independently associated with neonatal vitamin D deficiency were nulliparous, vitamin D supplements, maternal vitamin D binding protein level, and maternal VDR rs2228570. In addition, the analysis showed that maternal but not cord vitamin D deficiency was inversely associated with birth weight, head circumference, and length at birth. In contrast, cord but not maternal VDR rs2228570 was significantly associated with birth weight. Additionally, cord but not maternal GC rs4588 was significantly associated with the head circumference. A potential interaction effect between maternal VDR rs2228570 SNP and maternal vitamin D deficiency on head circumference was observed. In conclusion, a high prevalence of maternal and cord vitamin D deficiency was observed in this study. The analysis of factors associated with vitamin D deficiency supports supplementation as a potential strategy to decrease the risk of deficiency. The current work also consistently showed that maternal but not cord vitamin D deficiency was associated with the birth outcomes. In contrast, cord but not maternal SNPs were associated with several of the birth outcomes.